2019
DOI: 10.2478/fon-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem enhancement as a strategy for promoting the mental health and averting the occupational problems of nurses

Abstract: In recent years, shortage of nurses, high turnover rate, low self-worth, and team instability have become increasingly serious. With the development of positive psychology, more and more nursing managers have begun to attach great importance to the mental health of nurses. Self-esteem, as one of the core indicators of individual mental health, has received extensive attention from researchers in different fields since its inception. This paper reviews and summarizes the research status and development trends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Judge et al. (1998) and He et al. (2019) identified self-esteem threat as a potential antecedent of degraded work meaningfulness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Judge et al. (1998) and He et al. (2019) identified self-esteem threat as a potential antecedent of degraded work meaningfulness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An Indian study [ 20 ], which examined the relationship of AB and interpersonal communication satisfaction among 220 nurses, reported that AB had significant positive correlation with interpersonal communication satisfaction [ 20 ]. Self-esteem, a core predictor of subjective wellbeing and life satisfaction [ 26 ], reflects the individual’s overall assessment of self-worth and is considered as a critical element in healthy human development and functioning [ 27 ]. University students with low self-esteem clearly show negative professional attitudes and behaviors when they graduate [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has to do with the nurses' professional values, subjective wellbeing, and job happiness. Additionally, it prevents against job fatigue, bullying at work, anxiety, and depression [9]. To deal with challenges in life, emotional intelligence abilities can be taught and acquired [10].…”
Section: Introductionmentioning
confidence: 99%